Edukasi Manajemen Keuangan Santri dengan Metode 50/30/20 di Pondok Pesantren Al-Utsmani untuk Mencegah Budaya Israf - Achsan, Mochammad Achsan Auza'i; Khasanah, Uswatun; Faturrokhman, Muhammad Luki; Adinugraha, Hendri Hermawan (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The journal describes a financial management service offered to students at Pondok Pesantren Al Utsmani. The service is conducted using the 50/30/20 method and aims to increase students' awareness and ability in financial management, avoid the culture of israf, improve financial literacy, and provide a better understanding of financial management. The santri are introduced to the concept of financial management, its functions, and the application of the 50/30/20 method through a series of activities that include exposure, discussion, and material delivery. The aim is to enable the students to manage their finances wisely by allocating their income for primary needs, wants, and savings. This activity offers practical insights for students to effectively manage their finances during their education at the boarding school.